Current and future simulation in urological surgery training. Issue 3 (28th May 2019) - Berridge, Christopher; Jain, Sunjay; Biyani, Chandra Shekhar
Abstract : Simulation training offers new opportunities as the restrictions on traditional surgical training increase and the drive for higher quality and greater accountability continues. The authors describe different types of simulation, their role in surgical training and some of the benefits they may offer in the future.